2024
DOI: 10.1021/acsenergylett.3c02628
|View full text |Cite
|
Sign up to set email alerts
|

High-Capacity and Long-Cycling F-Ion Pouch Cells Enabled by Green Electrolytes

Yifan Yu,
Aming Lin,
Meng Lei
et al.

Abstract: Fluoride ion batteries (FIBs) hold promise as energy storage systems of high energy density and high safety. To proceed beyond the proof-ofconcept stage, however, working batteries with appealing specifications are yet to be demonstrated. Here, we present a rational design on liquid electrolytes for FIBs. The core idea is to employ a primary solvent, which enables the high solubility of fluoride salt CsF, and a solvation regulator, which can continuously tune the solubility of CsF. We propose ethylene glycol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The research on FIBs focused strongly on conversion-type cathode chemistries, i.e. metal/metal fluorides (Me/MeF x ) 9–15 which offer the highest theoretical capacities due to the possibility of taking part in a multi-electron conversion process. For example, Fichtner et al 16 reported the use of CuF 2 as the conversion-type electrode material in FIBs.…”
Section: Introductionmentioning
confidence: 99%
“…The research on FIBs focused strongly on conversion-type cathode chemistries, i.e. metal/metal fluorides (Me/MeF x ) 9–15 which offer the highest theoretical capacities due to the possibility of taking part in a multi-electron conversion process. For example, Fichtner et al 16 reported the use of CuF 2 as the conversion-type electrode material in FIBs.…”
Section: Introductionmentioning
confidence: 99%